Law Enforcement Against Traffic Violations And Electronic-Based Road Transport Through Electronic Traffic Law Enforcement - Ari Yuswan Triono (Jurnal Hukum Khaira Ummah, 2022)
This study aims to determine and analyze the law enforcement process for traffic violations and road transportation using Electronic Traffic Law Enforcement (ETLE) in the conception of the legal system and the effectiveness of law enforcement for traffic violations and road transportation by using Electronic Traffic Law Enforcement (ETLE) in order to avoid abuse of authority of Police officers at the Central Java Regional Police.The approach method in this study is an empirical juridical approach, the research specification is descriptive analytical. The data needed include primary data taken by interview method and secondary data by literature study method. The method of data analysis used descriptive qualitative analysis method. Based on the research concludedThe process of law enforcement for traffic violations and road transportation using Electronic Traffic Law Enforcement (ETLE) at the Central Java Regional Police starts from the Electronic Traffic Law Enforcement (ETLE) camera capturing images of vehicles committing violators on the road, after that from the screenshots of the surveillance cameras, The officer will then identify the vehicle data using Electronic Registration & Identification (ERI) as a source of vehicle data and the system will display the results of the synchronization of the violation data. The officer justifies the violation data that appears on the system, takes action on the violation resulting from the justification and sends it to the address of the violator according to the data in the ERI (Electronic Registration & Identification). Violators receive a confirmation letter and violators re-confirm both online/offline within 7 working days. The officer applies a STNK (Vehicle Number) block to ERI if the violator does not follow the procedure. Offenders receive a BRIVA SMS and pay the fine through the payment method provided within 7 (seven) working days after confirming. After payment is made, the violator applies for unblocking, then ERI will unblock it. Law enforcement of traffic violations and road transportation using Electronic Traffic Law Enforcement (ETLE) to avoid abuse of authority by police officers at the Central Java Regional Police has been effective.